Analysis on development characteristics and formation mechanism of karst collapse in Shakou Town, Yingde City of Guandong Province - Jianjun ZHAO (Zhongguo dizhi zaihai yu fangzhi xuebao, 2022)
In recent years, the collapse of hidden karst ground in the mountainous area of north Guangdong Province is increasing, which directly affects people's production and life. In a village of Shakou Town, Yingde City, where the geological environment conditions are complex and the quaternary overburden is thin, serious geological disaster of karst ground collapse has occurred due to the development of the karst cave and fault fracture zone and the connectivity between karst cave and karst cave. The direct contact between the bottom pebble layer and the overlying limestone of Tianziling Formation also accounts for the disastrous consequence. Based on the comprehensive analysis of the geological environment conditions of the village in Shakou Town, the development characteristics and formation mechanism of karst ground collapse from internal and external factors were analyzed. It is concluded that the loose cavern is formed by the loss of soil particles in the loose cavern under the interaction of long-term fluctuation of groundwater level, erosion and scouring; the strong alternation of surface water and groundwater forms the positive and negative pressure action; the ground collapse is caused by the loss of bearing capacity of the upper cavern. The conclusion of the research provides sufficient basis for making projects of preventing karst ground collapse scientifically.